PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 007 SERUSA MATI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Sri Murnita Sri Murnita; Syahrilfuddin '; Zariul Antosa Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was motivated by the low student learning outcomes in social studies. From the daily tests carried only 12 students who have mastery (48%) whereas those who did not complete 13 (52%) with KKM 60 While the average expected learning outcomes are 100% student mastery. The form of this research is a form of Classroom Action Research (CAR), which aims to improve outcomes for social studies fourth grade students of SD Negeri 007 Dead Serusa Bangko Rokan Hilir subdistrict. The problem of this study are Is the application of cooperative learning model to improve learning outcomes NHT IPS Elementary School fourth grade students Serusa 007 Dead Rokan Hilir District of Bangko? The subjects were fourth grade students of SD Negeri 007 Dead Serusa Rokan Hilir District of Bangko second semester of the school year 2013/2014 as many as 25 students consisting of 15 male students and 10 female students. Based on the results of research conducted, an increase in the number of students who reach the KKM of 12 people (48%) on the base score to 13 people (52%) of people on a daily repeat first in the first cycle and increased to 22 people (88%) on repeat II daily cycle II. An increase in average daily test results from the first study of 53.2 increased to 74.4 in the second daily test. An increase in the activity of the first meeting guru.Pada average teacher activity is 2.4, the second meeting of 3.2, 3.6 pertemua fourth and fifth meetings 4. activity was also an increase in the students' first encounter an average of 2.2 , 2.8 second meeting, the fourth meeting of 3.4, 3.8 and the fifth meeting Keywords: Cooperative Learning Model, Type Numbered Heads Together (NHT), Mathematics Learning Outcomes